Os reflexos da crise do capital na Previdência Social Brasileira - Pereira, Martha Bethânia Costa (2008)
This study analyzes the impact of capital crisis, on the Brazilian Social Security that starts to grow up at the end of 80’s, when in Brazil the neoliberal strategy is implemented. Occasion which 1988 constitution rights legally extends. The central axis of security crisis revolves around the financial imbalance which one would be making unfeasible the system in the future. This demonstrates that the highlighted crisis is associated with the economics, socials and politics determinations that have been built historically. The social protection stems from workers fight, unhappy with the established abuse relation capital and work, essential in the capitalist society. We grasp that new work relations are adopted, in the end of 20th Century, as strategy to solve the atual capital crisis. The strategy have direct relation with the exarcebation of the social issue, which results on the Social Security crisis.